2008
DOI: 10.1111/j.1365-2214.2008.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Parenting interventions and the prevention of unintentional injuries in childhood: systematic review and meta‐analysis

Abstract: Parenting interventions, most commonly provided within the home, using multi-faceted interventions appear to be effective in reducing unintentional child injury. Further research is required to explore the mechanisms by which parenting interventions reduce injury, the features of interventions that are necessary to reduce injury, and their generalizability to different population groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 51 publications
(197 reference statements)
1
43
0
1
Order By: Relevance
“…In addition, other factors possibly relevant to deaths caused by unintentional injuries, for example the characteristics of individual home environments such as the parental attitude toward child-rearing, the presence of siblings, economic context, and the regional conditions of residence such as access to medical facilities, were not considered. The results of a meta-analysis on parenting interventions and the prevention of unintentional injuries during childhood showed that intervention-arm families had a significantly lower risk of injury [28]. Moreover, in Japan, a population-based birth cohort study conducted for 42,144 individuals concluded that paternal involvement in childcare might be a useful predictive indicator of childhood injury [8].…”
Section: Study Limitationsmentioning
confidence: 99%
“…In addition, other factors possibly relevant to deaths caused by unintentional injuries, for example the characteristics of individual home environments such as the parental attitude toward child-rearing, the presence of siblings, economic context, and the regional conditions of residence such as access to medical facilities, were not considered. The results of a meta-analysis on parenting interventions and the prevention of unintentional injuries during childhood showed that intervention-arm families had a significantly lower risk of injury [28]. Moreover, in Japan, a population-based birth cohort study conducted for 42,144 individuals concluded that paternal involvement in childcare might be a useful predictive indicator of childhood injury [8].…”
Section: Study Limitationsmentioning
confidence: 99%
“…Interventions to support parents delivered by Health Visitors can reduce injury rates in both prospective studies37 and meta-analyses of randomised controlled trials 38. Meta-analysis of one-to-one parenting interventions, primarily conducted with high-risk or disadvantaged families, have demonstrated significantly lower risks of injury, as measured by parental self-report of either medically or non-medically attended injuries,39 40 but it is unclear if group-based programmes can achieve similar effects. Parental understanding of the relationship between injury risk and child behaviour and development is variable, and provision of educational anticipatory guidance has been recommended 41…”
Section: Introductionmentioning
confidence: 99%
“…1, 17-19 This is the first trial of home safety we are aware of that installed and maintained safety devices in all intervention homes of children to reduce exposure to prevalent hazards across multiple mechanisms of injury. 9, 10, 20, 21 …”
Section: Discussionmentioning
confidence: 99%